Evaluation of the XpertMTB/RIF for the Diagnosis of Pulmonary Tuberculosis Among the Patients Attending DOTS Center Parsa District of Nepal - Kurmi, Roshan; Rauniyar, Ramanuj; Manandhar, Krishna Das; Gupta, Birendra Prasad (Nepal Journal of Biotechnology, 2016)
Tuberculosis diagnosis and monitoring rely in Sputum microscopy of National Tuberculosis Programme, Nepal because of its low cost and easier to perform. Direct sputum microscopy is popular worldwide. Currently, there are 533 microscopy centres catering for sputum microscopy examination throughout the country. Most of the microscopy centres are established within government jurisdiction and remaining are established as non-governmental organization as well as private sectors. A cross-sectional study was conducted from July 2013 to January 2015. A total of 2091 patients were enrolled in the study who were attending the DOTS Centre in Parsa District of Public Health Office, Nepal. Smears stained with ZN stain methods were examined microscopically followed by the GeneXpert MTB/RIF assay. Out of 2091 suspected pulmonary TB patients enrolled for sputum microscopy and GeneXpert MTB/RIF for the confirmation of TB, the 1301(62.21%) were male and 790 (37.78%) were female. The maximum TB cases were from Parsa district (555, 26.5%). The comparative study of different diagnostic tools reveals the sensitivity of MTB/RIF was 95.50% (91.87, 97.82) and significantly higher than smear microscopy performed on the same fluid, which had a sensitivity of 61.97% (55.41, 68.21). Five of 127 smear-negative cases had MTB/RIF-positive un-centrifuged sputum, resulting in a specificity of 81.23% (75.95, 85.78), which was similar to smear microscopy 98.29 % (97.34, 98.97; p=0.121). The positive predictive value (PPV) and negative predictive value (NPV) of MTB/RIF were 96.85% (93.61, 98.72) and 94.95 % (93.52, 96.14), respectively. HIV co-infection did not impact sensitivity, specificity or liquid culture time to positivity (TTP). When MTB/RIF accuracy was evaluated using composite reference standard culture positivity from sputum, the sensitivity and specificity were similar to those obtained in the primary analysis using either definite TB versus possible and non-TB combined; definite and possible TB combined versus non-TB.